Tests of Drills during Drilling Holes into Alloy Wheels - Kyncl, Ladislav; Sadilek, Marek; Cep, Robert; Petru, Jana; Stancekova, Dana; Prochazka, Josef; Novacek, Pavel (Manufacturing Technology Journal, 2014)
This article is interested about drilling the holes to the alloy wheels. Tested were drills to drilling holes for screws and service holes. For screw holes was tested the three-stage drill with inserts from polycrystalline diamond. Drilled are two different diameters and the transition spherical or conical surface. The service holes were drilled with cemented carbide drill availible from Mapal labeled Mega-drill-Alu-180. During test, was modified the geometry of the drill and we watched what will be the effect of applied modification. Tested was seven variants of regrinding the drill. We evaluate the surface roughness, but also if the drill has the right position and not be pushed away from its axis. Finally was tested drill with three edges. This drill bit is from company Mapal labeled Tritan.
Keywords: drilling; drill; alloy wheels; aluminum alloy